Mitochondrial 16S Gene Polymorphism of Fiddler Crab, Gelasimus borealis (Crane, 1975) from Kulon Progo, Special Region of Yogyakarta - Arisuryanti, Tuty; Rokhmat, Laura Silka Karawina (Berkala Ilmiah Biologi, 2025)
The fiddler crab (Gelasimus borealis (Crane, 1975)) inhabits muddy or sandy intertidal zones in river estuaries or mangrove forests and is commonly found throughout Indonesia. However, studies on the abundance and genetic diversity of G. borealis in Indonesia, particularly regarding the mitochondrial 16S gene, remain limited. This study aims to analyze the genetic diversity of G. borealis from Kulon Progo based on the mitochondrial 16S gene. This study used a PCR method using 16Sar and 16Sbr primers, with stages comprising DNA isolation, amplification, electrophoresis, and sequencing. Data analysis was conducted to obtain nucleotide composition, genetic distance, genetic variation, haplotype network, and phylogenetic tree reconstruction using software programs such as GeneStudio, BLAST, MESQUITE, MEGA, DnaSP, BEAST, NETWORK, and GenAIEx. The results showed no genetic variation within the Kulon Progo population (intrapopulation analysis). However, interpopulation analysis using 16S sequence data of G. borealis from Hong Kong and Taiwan available in the GenBank database revealed genetic diversity, consisting of five haplotypes and five polymorphic sites, including two parsimony-informative sites. The haplotype and nucleotide diversity values were 0.857 ± 0.108 and 0.00368 ± 0.00055, respectively. Phylogenetic analysis indicated that the G. borealis population from Kulon Progo formed a distinct clade, separate from the Hong Kong and Taiwan populations, with a genetic distance of 0.45% but all are still conspecifics. This separation was also supported by the absence of haplotype sharing among the populations, as demonstrated by haplotype network and Principal Coordinate Analysis (PCoA). This study is expected to contribute to the development of a 16S gene reference library for the fiddler crab species G. borealis from Kulon Progo, which will be useful for species identification and conservation programs of this crab species.